Analisis Risiko Keselamatan dan Kesehatan Kerja pada Karyawan Proyek Konstruksi Pembangunan dengan Metode Modified House of Risk (HOR) (Studi Kasus: TPS Limbah B3 PT INKA (Persero) di Banyuwangi) - Sonny Putri, Nanda Salsabilla; Tranggono, Tranggono; Sari, Rizqi Novita (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze occupational safety and health risks in the construction project of the B3 waste TPS PT INKA (Persero) in Banyuwangi using the House of Risk (HOR) and integrated with the Software-Hardware-Environment-Liveware (SHELL) model. This HOR method consists of 2 (two) phases, namely HOR phase 1 which is used to identify risk events and risk agents that can occur in the company's operational processes and HOR phase 2 which is used to identify alternative risk mitigation strategies. The results of the study identified risks in HOR Phase 1, there were 27 risk events caused by 34 risk causes. Based on the ARP (Aggregate Risk Potential) calculation, 13 dominant risk causes were obtained. Then in HOR Phase 2, 18 mitigation steps were designed to prevent or effectiveness and degree of difficulty, the results of the mitigation effectiveness ranking based on the risk of difficulty (Effectiveness to Difficulty of Ratio - ETDk) were obtained with the highest value of carrying out routine preventive maintenance on carrying out routine supervision to ensure that workers follow the correct procedures and use PPE properly, and the last ranking was ensuring workers obtain relevant certification for special tasks that require special skills at the PT INKA (Persero) B3 Waste TPS in Banyuwangi).